Security Enhancement For Typical Corporate Networks - Hans Christian Marwi (TEMATIKA: Jurnal Penelitian Teknik Informatika dan Sistem Informasi, 2019)
In the midst of the growing use of the Internet and electronic commerce, security becomes more significant. This paper reported the results of a case study of security enhancement for a typical corporate network. This paper will discuss about the risks and priorities in security. Several methods that should be considered to be implemented in corporate networks will be given. In addition, suggestion to help the improvement will also be provided.